Regulation, markets, and poverty - Cook, Paul, 1944-; Mosedale, Sarah, 1956-; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : E. Elgar, 2007)
Regulation, Markets and Poverty incorporates the main policy implications arising from theoretical and empirical research into competition, regulation and regulatory governance in developing countries. This analysis often challenges conventional wisdom and draws on the work of leading experts from a range of disciplines.
Introduction -- Competition and innovation -- Designing competition policy -- Technological and trade competitiveness -- Why regulatory governance matters -- Regulatory policy transfer -- Regulating utilities in developing countries -- Problems of utility privatisation -- Regulating through ethical trade -- Regulatory impact assessment: improving regulatory quality in devloping countries -- Capacity building for regulation -- A regulators toolkit for capacity building -- Water subsidies and the poor -- Competition and regulation: the connection with poverty and income distribution.
Includes bibliographical references (p. 161-175) and index.
Keywords: Industrial policy -- Developing countries; Trade regulation -- Developing countries; Competition -- Developing countries; Poverty -- Developing countries; Electronic books